Characterization of Plant based spray dried powders using oil seed proteins and chokeberry extract from wine byproduct - Sana Ben-Othman; Uko Bleive; Hedi Kaldmäe; Alar Aluvee; Reelika Rätsep; Andres Sats; Nora Pap; Eila Järvenpää; Toonika Rinken (Scientific Reports, 2024)
Abstract Spray drying is a standard method for preserving bioactive ingredients and enhancing their storage stability. This study aimed to produce entirely plant-based spray-dried powders by using hemp, canola, and flax seed proteins, combined with maltodextrin, as wall material, while chokeberry extract from wine waste served as core material. We conducted a thorough analysis of the oil-seed proteins, examining their nitrogen solubility index, emulsification, and foaming capacities. The encapsulation process was evaluated based on its yield and efficiency. The spray-dried powders were further assessed through colour analysis, particle morphology and size distribution, hygroscopicity, and storage stability measurements. The encapsulation yield with oil-seed proteins ranged from 75.0 ± 6.2 to 78.5 ± 1.3%, and the efficiency from 58.4 ± 0.8 to 77.5 ± 1.9%. These plant-based spray-dried powders exhibited similar colour parameters, morphology, and stability to those of whey protein powders. The study highlights the significant potential of oil-seed proteins in producing plant-based spray-dried powders.